Analyzing COVID-19's Impact on Palm Oil and Biodiesel Investment Feasibility - Syamtori, Stanley; Munandar, Agus (Universitas Pendidikan Indonesia, 2024)
This research aims to explore the impact of the COVID-19 pandemic on investment feasibility in the palm oil and biodiesel industries, which are vital commodities in Indonesia and highly sensitive to economic conditions. Utilizing Fuzzy Analytical Hierarchy Process analysis and event studies, this research identifies the most critical aspects affecting the profitability of palm oil and biodiesel projects before and after the pandemic. The findings indicate that COVID-19 has a significant impact, particularly on Return on Investment and Modified Internal Rate of Return. The pandemic has increased costs and complicated risk management, impacting profitability and investment sustainability. These findings provide new insights into the challenges faced by the palm oil and biodiesel industries during the pandemic and offer a solid foundation for future strategic decision-making. The research underscores the importance of adaptive investment strategies, including the integration of robust risk management frameworks and resilience planning, to mitigate the effects of future economic shocks. Practical recommendations are provided for policymakers and stakeholders to incorporate comprehensive risk analysis and scenario planning into feasibility assessments, ensuring more sustainable investment outcomes. This study provides new perspectives on the impact of the pandemic on industries that are heavily dependent on global and local economic conditions, providing an analytical framework to measure the impact of significant events on investments in these sectors.